Fluoroquinolone-specific resistance trajectories in E. coli and their dependence on the SOS-response - Lisa Teichmann; Sam Luitwieler; Johan Bengtsson-Palme; Benno ter Kuile (BMC Microbiology)
Abstract Background Fluoroquinolones are indispensable antibiotics used in treating bacterial infections in both human and veterinary medicine. However, resistance to these drugs presents a growing challenge. The SOS response, a DNA repair pathway activated by DNA damage, is known to influence resistance development, yet its role in fluoroquinolone resistance is not fully understood. This study aims to unfold the mechanisms of fluoroquinolone resistance by investigating the impact of the SOS response on bacterial adaptation. Results We exposed Escherichia coli to four fluoroquinolones—ciprofloxacin, enrofloxacin, levofloxacin, and moxifloxacin. Using a recA knockout mutant, deficient in the SOS response, as a control, we assessed how the presence or absence of this pathway affects resistance development. Our findings demonstrated that the rate of resistance evolution varied between the different fluoroquinolones. Ciprofloxacin, enrofloxacin, and moxifloxacin exposures led to the most evident reliance on the SOS response for resistance, whereas levofloxacin exposed cultures showed less dependency. Whole genome analysis indicated distinct genetic changes associated with each fluoroquinolone, highlighting potential different pathways and mechanisms involved in resistance. Conclusions This study shows that the SOS response plays a crucial role in resistance development to certain fluoroquinolones, with varying dependencies per drug. The characteristic impact of fluoroquinolones on resistance mechanisms emphasizes the need to consider the unique properties of each antibiotic in resistance studies and treatment strategies. These findings are essential for improving antibiotic stewardship and developing more effective, tailored interventions to combat resistance.